Role of integrating cannabinoids and the endocannabinoid system in neonatal hypoxic-ischaemic encephalopathy - Xiao, Jie; Zhou, Yue; Sun, Luqiang; Wang, Haichuan (Frontiers in Molecular Neuroscience, 2023)
Neonatal hypoxic-ischaemic events, which can result in long-term neurological impairments or even cell death, are among the most significant causes of brain injury during neurodevelopment. The complexity of neonatal hypoxic-ischaemic pathophysiology and cellular pathways make it difficult to treat brain damage; hence, the development of new neuroprotective medicines is of great interest. Recently, numerous neuroprotective medicines have been developed to treat brain injuries and improve long-term outcomes based on comprehensive knowledge of the mechanisms that underlie neuronal plasticity following hypoxic-ischaemic brain injury. In this context, understanding of the medicinal potential of cannabinoids and the endocannabinoid system has recently increased. The endocannabinoid system plays a vital neuromodulatory role in numerous brain regions, ensuring appropriate control of neuronal activity. Its natural neuroprotection against adult brain injury or acute brain injury also clearly demonstrate the role of endocannabinoid signalling in modulating neuronal activity in the adult brain. The goal of this review is to examine how cannabinoid-derived compounds can be used to treat neonatal hypoxic-ischaemic brain injury and to assess the critical function of the endocannabinoid system and its potential for use as a new neuroprotective treatment for neonatal hypoxic-ischaemic brain injury.